2015
DOI: 10.1039/c5cp00383k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry at highly oriented pyrolytic graphite (HOPG): lower limit for the kinetics of outer-sphere redox processes and general implications for electron transfer models

Abstract: Original citation:Zhang, Guohui, Cuharuc, Anatolii S., Güell, Aleix G. and Unwin, Patrick R.. (2015) Electrochemistry at highly oriented pyrolytic graphite (HOPG) : lower limit for the kinetics of outer-sphere redox processes and general implications for electron transfer models. Physical Chemistry Chemical Physics (Number 17). pp. 11827-11838. Permanent WRAP url: http://wrap.warwick.ac.uk/67805 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 104 publications
(253 reference statements)
3
87
0
Order By: Relevance
“…63 Comparison of experimental to computed diffusional waves (using precise diffusion coefficients) showed that the experimental currents exceeded the simulated ones (see SI, Section S-2, Figure S-1 (c)), whereas the reverse scan voltammetry fitted quite well. Thus, while FcTMA + adsorbs at the HOPG electrode, FcTMA 2+ that is produced does not adsorb appreciably and a significant proportion of FcTMA 2+ produced by the oxidation of adsorbed FcTMA + , diffuses away from the electrode on this timescale.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…63 Comparison of experimental to computed diffusional waves (using precise diffusion coefficients) showed that the experimental currents exceeded the simulated ones (see SI, Section S-2, Figure S-1 (c)), whereas the reverse scan voltammetry fitted quite well. Thus, while FcTMA + adsorbs at the HOPG electrode, FcTMA 2+ that is produced does not adsorb appreciably and a significant proportion of FcTMA 2+ produced by the oxidation of adsorbed FcTMA + , diffuses away from the electrode on this timescale.…”
Section: Resultsmentioning
confidence: 91%
“…Fresh HOPG basal surfaces were prepared by gently pressing down Scotch tape on to the sample and pullingoff the top layers, as reported extensively in the literature. 33,[60][61][62][63] Cyclic Voltammetry and SECM Instrumentation cm 2 ) with the counter and reference electrode placed into the droplet. 63 An advantage of this electrochemical cell is that it can be assembled and used within seconds of sample cleavage, 63 minimizing surface contamination.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…[13][14][15] This is particularly true of graphite, which comprises stacked graphene layers with weak van der Waals force present between the layers. 7 While outer sphere redox processes, and some more complex electron-proton coupled processes, occur readily at the basal structure of graphite, [16][17][18][19][20][21] electrocatalytic (bond-breaking) reactions often require additional efforts to promote the electrochemical activity. There are 3 broad, and somewhat interrelated, approaches and effects to consider: (i) selective doping of sp 2 materials by various heteroatoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…22,40,41 In the case of outer sphere redox processes, electron transfer rates are at least as fast at HOPG as on platinum. 27 The studies reported herein on the electrochemical oxidation of NADH at HOPG and oxygen-terminated pBDD reinforce, and amplify, the recent models on the properties and activity of these electrode materials, while also providing detailed new insights on adsorption and surface fouling (contamination) processes. These measurements are complemented with high resolution scanning electrochemical cell microscopy (SECCM) 42,43 experiments to map the electrochemical activity of HOPG and pBDD and confirm the macroscopic findings.…”
Section: Introductionmentioning
confidence: 99%
“…It comprises of extensive basal terraces with a low density of point defects, 26,27 and a step edge density that depends on the grade (quality) of the HOPG. 28,29 Although early work considered the basal surface of HOPG to have ultra-low (or no) electrochemical activity, 27,[29][30][31][32][33][34][35][36][37][38][39] recent studies have highlighted the high activity of the basal surface for both simple redox reactions and more complex coupled electron-proton transfer processes. 22,40,41 In the case of outer sphere redox processes, electron transfer rates are at least as fast at HOPG as on platinum.…”
Section: Introductionmentioning
confidence: 99%